And the Oscar Goes to Peripheral Blood Film for the Detection of Lead Poisoning in a Complicated Toxic Patient: A Case Report with a Review of Laboratory Clues - Amir Zamani; Ehsan Sarraf Kazerooni; S. Saeed Kasaee; Mohammad Hossein Anbardar; Sahand Mohammadzadeh; Golsa Shekarkhar; Neda Soleimani (Case Reports in Medicine)
Background. Peripheral blood smear examination is an invaluable laboratory test, which provides the complete hematologic and/or nonhematologic picture of a case. In addition to verifying the results of automated cell counters, it has the potential to identify some pathologic and morphologic changes that remain hidden using the cell counters alone. Case Presentation. A 40-year-old man with a three-year history of alcohol intake and marijuana abuse presented with severe lower extremities of the bone and abdominal pain. Physical examination showed high blood pressure, high pulse rate, and abdominal tenderness. He underwent extensive laboratory and imaging tests, and cholecystectomy and bone marrow studies were associated with no definite diagnosis. Right after all these invasive, expensive, and time-consuming investigations during a month, finding coarse basophilic stippling in the red blood cells in the peripheral blood smear by an expert led to the final diagnosis. Elevated blood lead level and the presence of ring sideroblasts in the bone marrow study confirmed the diagnosis of lead poisoning, and the patient responded well to chelator therapy in a short period. Conclusion. This case clearly showed the value of peripheral blood smear review and its impact on patient care. In order not to lose the cases, laboratories are recommended to design their own policy for peripheral blood smear review. The peripheral blood smear is the fastest, simplest, and most available screening test, which can prevent many misdiagnoses and malpractices. It provides rich morphological information, among which basophilic stippling is highly suggestive of lead poisoning.